Degradation Studies of Insecticide Imidacloprid Using Fluidized Bed Photocatalytic Reactor - Srivastava, Shashank (My University, 2013)
Disposal and treatment of wastewater containing bio-recalcitrant such as insecticide imidacloprid is a matter of great concern. Various conventional and existing treatment technologies could only concentrate the pollutants by transferring them from one phase to the other. Moreover, the conventional treatments could also generate toxic secondary pollutants too, which further adds up the operational costs. Hence there is an urgent need to look for the advanced and emerging technologies which could completely mineralize the irrespective pollutants. Advanced Oxidation Process has emerged one such technology for treatment of such bio-recalcitrant compounds, which relies on the principle of production of high oxidation potential hydroxyl ions which ultimately converts the toxic compounds to non-toxic end products. One such approach in AOP‟s include Fixed Bed Photocatalysis to treat pesticidal wastewater using suitable catalyst such as TiO2 P-25 Degussa. Since the mode of catalyst usage and its recovery is a matter of concern from the economical point of view, hence the immobilization of catalyst onto suitable support material is the need of hour. Pebbles made out of cement and sand mixture proved to be mechanically robust, chemically inert and cheap immobilizing material which has the very high adsorptive capacity towards the catalyst with negligible catalyst attrition rate. In the present study, 25 mg/L of pesticide imidacloprid solution was treated under optimized conditions and various parameters and degradation feasibilities were analyzed. Various diameters of immobilizing material were tried and the optimum results were found at 0.75 cm diameter along with catalyst loading of 3% (w/w), degradation was found out to be 81.1%. Effect of oxidant dose was also studied and the degradation occurred was as high as 88% under the optimum dosage of 4.8 ml/L.
Master of Technology Dissertation
Keywords: Imidachloprid; Photocatalysis; Fluidized bed; Degradation